2020
DOI: 10.3390/genes11111265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic-Based Hypertension Subtype Identification Using Informative SNPs

Abstract: In this work, we proposed a process to select informative genetic variants for identifying clinically meaningful subtypes of hypertensive patients. We studied 575 African American (AA) and 612 Caucasian hypertensive participants enrolled in the Hypertension Genetic Epidemiology Network (HyperGEN) study and analyzed each race-based group separately. All study participants underwent GWAS (Genome-Wide Association Studies) and echocardiography. We applied a variety of statistical methods and filtering criteria, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Our work, as well as previous studies [3,34,35] that use clustering techniques to study the population structure of the SARS-CoV-2 virus, has proved to be a valuable supplemental tool in phylogenetic analyses. For future work, we plan to further apply soft clustering techniques to better account mixtures in clusters, the efficacy of which has been showcased by previous studies in multiple fields [36][37][38][39][40][41][42]. In addition, clustering ideas can be used for further study of variant population structures in specific regions of these fast-growing viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Our work, as well as previous studies [3,34,35] that use clustering techniques to study the population structure of the SARS-CoV-2 virus, has proved to be a valuable supplemental tool in phylogenetic analyses. For future work, we plan to further apply soft clustering techniques to better account mixtures in clusters, the efficacy of which has been showcased by previous studies in multiple fields [36][37][38][39][40][41][42]. In addition, clustering ideas can be used for further study of variant population structures in specific regions of these fast-growing viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that genetic factors are responsible not only for blood pressure elevation but also play a profound role in the interindividual variability in drug response, offering an opportunity for pharmacogenomic investigation and potential individualized drug therapy [ 18 , 19 ]. Therefore, it has been speculated that a patient’s inter-individual genetic variation can be used to understand the pathophysiology of the disease and that this pharmacogenomics approach may have the potential of individualizing HTN drug therapy based on the patient’s genetic background [ 20 , 21 ]. For example, Guo et al, [ 22 ] and Choi et al, [ 23 ] have reported successful examples of genetic polymorphisms on blood pressure response to antihypertensive therapies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al, [ 22 ] and Choi et al, [ 23 ] have reported successful examples of genetic polymorphisms on blood pressure response to antihypertensive therapies. Recently, Ma et al [ 21 ] reported that various informative genetic variants can be utilized for the identification of subtypes of hypertension. These studies have highlighted the importance of understanding the biological basis of the disease and the contribution of genetic variations in the development and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 2 prior studies have assessed genetic subtyping of hypertension. The first study by Ma et al 6 used a traditional subtyping algorithm, non-negative matrix factorization (NMF), to find genetic hypertension components in 1187 hypertensive participants of the Hypertension Genetic Epidemiology Network. 26 Hypertension Genetic Epidemiology Network is a cross-sectional family study aiming to identify and characterize the genetic basis of familial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to clinical characteristics, genetic variants are fixed and known to predict the onset of polygenic diseases such as type 2 diabetes. 5 Based on genetic variants, both Ma et al 6 (N=1187) and Luo et al 7 (N=660) subtyped hypertensive individuals and uncovered genetic hypertension components with differing echocardiographic measurements. While these 2 studies have pioneered a classification of hypertension genetics, they are limited in sample size and by phenotype data that were mainly limited to echocardiographic variables.…”
mentioning
confidence: 99%